1990
DOI: 10.1176/appi.psychotherapy.1990.44.4.552
|View full text |Cite
|
Sign up to set email alerts
|

No Safe Place: Parental Alcoholism and Adolescent Suicide

Abstract: A child growing up in an alcoholic home develops either little self-consolidation (I-ness) and efficacy (I can) or a distorted self (I am insignificant). This results in a desperate search for a soothing-object (We-ness). The sadomasochistic behaviors, which a youth witnesses and is subjected to, become internalized as survival skills, but ultimately fail. These factors set the stage for a destructive modus operandi. When there is peer group attachment pressure, this teen does not find security when questionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Adolescent suicide and parental alcoholism have been associated (7). Men with a multi-generational history of alcoholism manifested a high prevalence of diverse psychiatric conditions (8).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent suicide and parental alcoholism have been associated (7). Men with a multi-generational history of alcoholism manifested a high prevalence of diverse psychiatric conditions (8).…”
Section: Introductionmentioning
confidence: 99%
“…So it becomes imperative that children of alcoholics find secure attachments with other people in order to successfully navigate through their adolescence and become self-sufficient young adults. Thus, some of those children are able to fill those feelings of emptiness when they have relationships and make attachments to peers and non-family individuals (Meyer & Phillips, 1990). A study conducted by Cavell, Jones, Runyan, Constantin-Page, and Velasquez (1993), showed that it is not uncommon for children of alcoholics to ultimately be less secure in their relationships if they had an "alcohol-dependent" father, compared to children of similar age who had "non-alcohol-dependent" fathers.…”
Section: Chapter 2 Literature Review Theoretical Frameworkmentioning
confidence: 99%
“…There are strong connections to drug abuse and suicide attempts in children of alcoholics especially when the mother is the drinking parent (Anda et al, 2002). These self-destructive behaviors are not uncommon consequences of a child who have grown up in an alcoholic home (Meyer & Phillips, 1990); however, one study argued that this behavior was only indicative of children who have had three or more alcoholic family members in their lives (Barnow, Schuckit, Smith, Preuss, & Danko, 2002).…”
Section: Externalizing Behaviorsmentioning
confidence: 99%
See 2 more Smart Citations